METHODOLOGICAL BASIS OF REALIZATION OF INTERSUBJECT COMMUNICATIONS OF PHYSICS WITH THE NATURAL SCIENCES IN SCIENCE EDUCATION - Jumadillayevа А.К.; Jumadillayev Қ.Н.; Jakupova Ж.О.; Kozybay А.Қ. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
The article deal with the problems of implementing intersubject communications of physics with the natural sciences in natural science education. The relevance, significance, goals, methods and forms of the implementation of intersubject communications of physics with the natural sciences in natural science education are established. It is shown that the only way for future teachers of physics to form deep and systematic knowledge is to prepare them for the implementation of interdisciplinary knowledge. Intersubject communication should be considered as a manifestation in the educational process of the relationship of different sciences. No single science, no matter how significant and developed it may be, can create a holistic view of the world, but can only take part in its formation. Interdisciplinary communication, acting as a bridge connecting all objects and sciences, opens up wide opportunities for the development of specific sciences and the scientific picture of the world. Therefore, interdisciplinary communication, as a prerequisite for the successful development of scientific knowledge, and as a method of searching for new results and cognition, reveals to students the way of understanding the world, and thereby ensures conceptual thinking.